Ground-state tautomerism and rotational isomerization in 4,5-dimethyl-2-(2-hydroxyphenyl)imidazole in the gas phase and in polar solvents: a theoretical study of the aromaticity, intramolecular hydrogen-bond strength and differential solute-solvent interactions - Clark, Timothy; et al. (Physical Chemistry Chemical Physics, 2001)
Ground-state tautomerism and rotational isomerization in 4,5-dimethyl-2-(2-hydroxyphenyl)imidazole in the gas phase and in solution have been investigated by means of quantum mechanical calculations, NMR and steady-state fluorescence spectroscopy. In the gas phase, the cis-enol form is the most stable species, followed by the trans-enol and the keto forms. Several theoretical approaches were employed to characterize the electronic structure of the different isomers in the gas phase at the RB3LYP/6-31 + G* level of theory. The observed behavior could be rationalized according to the different weights of the resonance and the hydrogen-bond energies in the overall energy of each isomer. The hydroxyphenyl rings of the trans-enol and the cis-enol forms exhibit a nearly aromatic structure, whereas the electronic structure of the keto-form shows a higher degree of localization. In turn, it was found that the intramolecular hydrogen bond shows similar strength in the cis-enol and keto-forms, whereas this interaction is very weak in the trans-enol form. Polar solute-solvent non-specific interactions were modeled through the Onsager, SCI-PCM and COSMO methods based on ab initio and semiempirical Hamiltonians. In solution, the keto-form is stabilized by its much greater solute-solvent electrostatic interaction through its dipolar term and the aromatization of its phenyl ring. The trans-enol form is mainly stabilized by electrostatic interactions through higher multipolar terms than dipolar and specific solute-solvent interactions through the lone pair of the imidazole N-3.